On equivalence of pairs of matrices, which determinants are primes powers, over quadratic Euclidean rings - Ladzoryshyn, N.B. (Carpathian Mathematical Publications, 2013)
We establish that a pair of matrices, which determinants are primes powers, can be reduced over quadratic Euclidean ring K=Z[k] to their triangular forms with invariant factors on a main diagonal by using the common transformation of rows over a ring of rational integers Z and separate transformations of columns over a quadratic ring K.